A Novel Stabilizing Controller Design for Singular Delayed Systems: An Optimization Approach - Parlakci, Mehmet Nur Alpaslan (IEEE, 2018)
This paper studies the problem of stabilization for a class of linear singular time-delay systems. First, a delay-dependent stability criterion is developed within the context of Lyapunov stability theory and linear matrix inequalities. The stability result is then extended to obtain a stabilizing state-feedback controller within the bilinear matrix inequalities (BMI) framework. Employing the cone complementary linearization approach, the synthesis problem can be resolved through a set of LMI conditions. Several numerical examples are presented to illustrate the application of the theoretical results.
6th International Conference on Control Engineering and Information Technology (CEIT) -- OCT 25-27, 2018 -- Istanbul, TURKEY
Keywords: Singular Systems; Time Delay; State Feedback; Bilinear Matrix İnequality; Cone Complementary; Optimization; Dependent Robust Stability; Static Output-Feedback; Descriptor Systems; Criteria